Pendidikan Islam di Indonesia Pasca Kemerdekaan - Hs, Fatimah; Zainuddin, Fathul Muin; Arkan, Arnadi (Jurnal Ilmiah Edukatif, 2026)
After the proclamation of Indonesian independence in 1945, Islamic education played a significant role in the formation of national identity and the development of Indonesian society. This research aims to provide insight into the development of Islamic education in post- independence Indonesia and the relevance of policy in maintaining the existence of Islamic education within the national education framework. The research method used is qualitative with library research. Data analysis uses content analysis content. The main findings include the goals of Islamic education to shape religious and national character, improve the quality of Islamic education, encourage tolerance between religious communities, produce a generation that makes positive contributions, and develop research in the Islamic context. The policies implemented after independence recognized the importance of Islamic education in forming the character of citizens in accordance with the values of Pancasila. During the Old Order, the government focused on regulating nationalist values and the ideology of national and state life through education.